Pelapisan Logam Menggunakan Plasma - Wijono; Bob Alvin Sidabutar; Waru Djuriatno (Jurnal Intake : Jurnal Penelitian Ilmu Teknik dan Terapan, 2019)
One of the ways to improve the quality of the material is by using the thin layer deposition techniques on the material surface. DC magnetron sputtering is one of the methods frequently used to do so. This method uses plasma to create a thin layer on the material's surface. In this research, flyback circuit is used to generate plasma. This research examines the effects of electrodes’ gap and sputtering process time on the width of marks that appear on the substrate’s surface. The electrodes’ gap varies in range of 1, 2, 3, and 4 cm, whereas the sputtering process time varies in range of 36, 72, 108, 144, and 180 minutes. The substrate used in this research is iron and the coating materials used are aluminium and copper. This research uses plate-shaped electrodes in the coating process. The sputtering process resulted in the appearance of marks on the substrate’s surface. The marks were compared qualitatively with every gap range of electrodes, sputtering process time, and the coating material used. Next, they were categorized into 6 groups according to the thickness of the marks’ layer in order to obtain quantitative data which were then made into graphics. The results of this research show that silver coating material takes the shortest time to coat iron substrate, which is 36 minutes. In 36 minutes, the marks produced by silver coating fall under the group with the highest marks, compared to other coating materials. This research also shows that alteration of the electrodes' gap will affect the voltage of electrodes and the coating’s thickness groups. The further the gap between the electrodes, the higher the electrodes’ voltage and the coating’s thickness groups will be.